Effects of lower limb strengthening on balance and function in persons who suffered a stroke - Fernandes, B (2012)
Introduction - Cerebrovascular diseases, and among them, cerebral vascular accidents, are one of the main causes of morbidity and disability at European Union countries. Clinical framework resulting from these diseases include important limitations in functional ability of the these patients Postural control dysfunctions are one of the most common and devastating consequences of a stroke interfering with function and autonomy and affecting different aspects of people’s life and contributing to decrease quality of life. Neurological physiotherapy plays a central role in the recovery of movement and posture, however it is necessary to study the efficacy of techniques that physiotherapists use to treat these problems. Objectives - The aim of this study was to investigate the effects of a physiotherapy intervention program, based on oriented tasks and strengthening of the affected lower limb, on balance and functionality of individuals who have suffered a stroke. In addition our study aimed to investigate the effect of strength training of the affected lower limb on muscle tone.